Pemenuhan Hak Narapidana Ibu Menyusui Di Lembaga Permasyarakatan Kelas IIa Sungguminasa: Perspektif Mazhab al-Syafi’i dan Maliki - Ramadhani, Herlina; Mustafa, Zulhas'ari (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
The purpose of this study was to examine. How are the conditions and treatment of prison officers for nursing mother inmates at the Class IIA Sungguminasa Penitentiary. What are the views of the Al-Shafi'i and Maliki schools regarding nursing mothers inmates. The method used is a qualitative research method that seeks to obtain information about the object under study according to the reality that exists in prisons. By using the interview method, and data collection the results showed that, The majority of the occupants of the prison for breastfeeding mothers in Sungguminasa class IIA were 3 people, namely Mrs. Satria Ria, Megawati and Mega Sulfia. Number 12 of 1995 which states that the rights of inmates who are breastfeeding mothers are fulfilled as long as they are undergoing a period of coaching. From the point of view of the Al-Shafi'i and Maliki schools, nursing mothers have carried out their obligations as mothers according to the views of the al-Shafi'i and Maliki schools. The implication of this research is that the coaching system has complied with the requirements and procedures for the implementation of the rights of the inmates who apply in accordance with Law No. 12 of 1995 concerning Corrections. The opinions of the Al-Shafi'i and Maliki schools in the application of the Class IIA Sungguminasa Women's Correctional Institution are carried out according to the views of the al-Shafi'i and Maliki schools which even though they are carrying out coaching, they still carry out their obligations as mothers, namely breastfeeding the baby. As for the form of deficiency, namely the lack of space for prisoners so that they are in one room whose number is outside of what they should be.